PENGARUH AKUNTABILITAS, KETIDAKPASTIAN LINGKUNGAN, KOMITMEN PIMPINAN, DAN PENGENDALIAN INTERNAL TERHADAP PENERAPAN TRANSPARANSI PELAPORAN KEUANGAN (Studi Empiris Pada SKPD Provinsi Riau) - Rahmad Bintang Shabri Asroel; Yessi Mutia Basri; Susilatri ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The purpose of this research was to examine the influence accountability, environmental uncertainty, leader commitment, and internal control on transparency of financial reporting. This research is expected to help the government in order to improve the transparency of financial reporting increasingly better in the future. The sample used in this research are the echelon IV and accounting staff in Riau Province Government. Data was collected through questionnaire survey method. The data was collected by using 96 questionnaires that spread to 32 SKPD (regional work units and only 80 questionnaire could be analyzed. Data were analyzed by using multiple regression (multiple regression) and moderate regression (Moderate Regression Analysis-MRA) with the help of a computer program SPSS version 17.0. The results showed that accountability, environmental uncertainty, leader commitment, and internal control had significant influence on transparency of financial reporting.Keywords: accountability, environmental uncertainty, leader commitment, internal control, and transparency of financial reporting.